The association of race with thyroid eye disease presentation and outcomes - Wang, Diane; Marous, Charlotte; Celiker, Pelin; Deng, Wenyu; Kristoferson, Eva; Elsayed, Ali; Shinder, Roman; Hodgson, Nickisa (Frontiers in Ophthalmology, 2024)
Introduction Classification of thyroid eye disease (TED) is largely based on guidelines developed in Europe and North America. Few studies have investigated the presentation and treatment of TED in Black populations. The objective is to examine the manifestations of TED in secondary and tertiary care center-based populations with a significant proportion of Black patients. Materials and methods Retrospective chart review identifying patients with a reported race/ethnicity and a presenting clinical diagnosis of TED at Kings County Hospital and SUNY Downstate Medical Center and affiliated clinics from January 1, 2010 through July 31, 2021. Main outcome measures include age of disease onset, sex, smoking status, insurance status, postal code of residence, clinical exam features, number of follow-up visits, length of follow-up, and treatments received. Results Of the 80 patients analyzed, 49 were Black (61.2%) and 31 were White (38.8%). Between Black and White patients, there were differences in the mean age of presentation (48.1 [range 21-76] vs 56.8 [range 28-87] years, P=0.03), insurance status (51.0% vs 77.4% private insurance, P=0.02), and mean follow up length among those with multiple visits (21.6 [range 2-88] vs 9.7 [range 1-48] months, P=0.02). The distribution of EUGOGO scores were not significantly different between Black and White patients. On initial presentation, fewer Black patients had chemosis (OR 0.21, 95% CI, 0.08 to 0.57, P=0.002), and caruncular swelling (OR 0.19, 95% CI, 0.06 to 0.59, P=0.002) compared to White patients. During the overall disease course, fewer Black patients had subjective diplopia (OR 0.20, 95% CI, 0.07 to 0.56, P=0.002), chemosis (OR 0.24, 95% CI, 0.09 to 0.63, P=0.004), and caruncular swelling (OR 0.18, 95% CI, 0.07 to 0.51, P=0.001) compared to White patients. Black patients received oral steroids (42.9% vs 67.7%, P=0.03), intravenous steroids (18.4% vs 16.1%, P=0.8), orbital decompression surgery (16.7% vs 6.5%, P=0.19), and teprotumumab (22.9% vs 22.6%, P=0.99) at similar rates. Discussion Black patients presented with fewer external exam findings suggestive of active TED compared to White patients, but the rate of compressive optic neuropathy and decompression surgery were similar in the two groups. These differences may be due to disease phenotypes, which warrant further study.